Difficult-to-treat axial spondyloarthritis patients - Tahir Saygın Öğüt; Funda Erbasan; Mehmet Fatih Şahiner; Mine Nokay; Ayşe Yörük Öğüt; Melis Dilbil; Mustafa Ender Terzioğlu; Veli Yazısız (Archives of Rheumatology, 2024)
Objectives: This study aimed to formulate D2T (difficult to treat) criteria for axial spondyloarthritis (AxSpA) patients and identify the prevalence of D2T patients and their characteristics. Patients and methods: The cross-sectional study was conducted with 166 AxSpA patients (93 males, 73 females; mean age: 47.1±12.9 years; range, 19 to 78 years) between February 2023 and March 2023. The criteria were based on patients treated according to the European Alliance of Associations for Rheumatology (EULAR) recommendations for AxSpA. Entry criteria were treatment failure to ≥2 biological/targeted synthetic disease-modifying antirheumatic drugs with two different mechanisms of action or ≥3 biological/targeted synthetic disease-modifying antirheumatic drugs. Potential preliminary factors for D2T criteria were analyzed, and the characteristics of the subjects matching D2T criteria were compared with those of others. Results: One hundred forty-two ankylosing spondylitis patients and 24 nonradiographic AxSpA patients were included in the study. The rate of fulfilling the D2T criteria was 22.9% (n=38) among AxsPA patients treated with biological agents. The potential D2T criteria were met by 23.2% of ankylosing spondylitis and 20.8% of nonradiographic AxSpA patients. Baseline characteristics, such as sex, age, diagnosis age, occupation, and education, of D2T patients were not statistically different from other patients. The prevalence of fibromyalgia was higher in D2T patients (p<0.001). Disease activity indices and acute phase response indicators were higher and quality of life was worse in D2T patients. Conclusion: There was a considerable amount of AxSpA patients fulfilling the D2T criteria despite new and effective treatment agents.